Entrepreneurship Training Management Based on Life Skills at the Community Learning Center "Tim Suara Masyarakat Dawuan", Cikampek District, Karawang Regency - Amelia, Anggi; Sudrajat, Tatang; Yuliaty, Farida (Jurnal Manajemen Bisnis, 2025)
In the era of globalization, life skills are a key factor in improving human resource quality, particularly in entrepreneurship. PKBM Tim Suara Masyarakat Dawuan, Karawang Regency, implements entrepreneurship training based on life skills to strengthen learners’ economic independence. This study applied a descriptive qualitative approach through in-depth interviews, observations, and documentation, involving four informants: PKBM managers, training tutors, and program alumni. Data analysis was conducted systematically using Nvivo 15. The findings reveal that training management at PKBM Tim Suara Masyarakat Dawuan is carried out through careful planning based on learner needs, participatory learning methods, and continuous evaluation. Supporting factors include financial assistance from external partners, adequate facilities, and the active role of tutors in motivating participants. However, challenges remain, particularly low awareness among school-age learners who struggle to recognize the importance of life skills and economic independence. This study contributes to the limited literature on life skill-based entrepreneurship training in non-formal education in Indonesia. Practically, it provides strategic recommendations for PKBM to maximize training success, enabling the development of independent, creative, and competitive graduates.